FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA DESTINASI WISATA MONUMEN YOGYA KEMBALI TAHUN 2009-2012 - , JAYA SAMIAJI; , Drs. Bambang sunaryo, M.sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to identify and describe the factors that affect the performance of tourist destinations at Yogya Kembali Monument. Yogya Kembali Monument is a tourist destination and educational facilities are located in Yogyakarta. Yogya Kembali Monument is a monument that contains the struggles of the people of Indonesia and Yogyakarta in particular in the fightfor Indonesia's independence. The number of tourists visiting Yogya Kembali Monument fluctuated. The travelers up and down is influenced by the sights, marketing, infrastructure, tourist destinations, tourist perception This study is a qualitative study, the research done by observation, interviews both with tourists and with managers of Yogya Kembali Monument, and the questionnaire data were collected, identified and then proceed to analyze the data. This analysis method will be used in describing the factors that influence the rise and fall of the number of tourists travel destinations Yogya Kembali Monument. These results indicate that the tourist attraction has an influence on the performance of tourist destinations, with the development of tourist attractions, tourist numbers increased significantly, it is also supported by the marketing tourist perceptions conducted and the suitability of the real situationencountered.